(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Refractory glaucoma is a challenge for ophthalmologists. The disease can progress, leading to permanent blindness or pain that affects the patient’s life. At that time, ciliary body destruction can be proposed and the method of implementation is additional transscleral ciliary micropulse photocoagulation plus using a diode laser (810 nm) combining 2 techniques sweeping and discrete spot for intraocular pressure lowering and does not have serious complications of patients with uncontrolled IOPs who had previous micropulse transscleral photocoagulation with only performing techniques sweeping. Therefore, we conducted a survey of evaluating the efficacy of micropulse transscleral cyclophotocoagulation plus in treating refractory glaucoma. Methods: Prospective study involved with uncontrolled clinical trial. The main outcome measurement was IOP at 1day, 1 week, 1 month, 3 months, 6 months post-procedure, with success defined as a 20% reduction in baseline IOP or IOP from 6 to 25 mmHg, and no need for further reoperation. Results: The study included 39 eyes with refractory glaucoma, average age was 55.2 ± 12.9 years, ratio of male and female = 1,2:1. The diagnosis of neovascular glaucoma accounted for the highest rate in the study group (38,5%). Visual acuity from no perception of light to count fingers 0,5 m. All diseases have CDR = 1.0. The average preoperatively IOP was 43,1 ± 9,6 mmHg and posttreatment 6 months were 20,7 ± 13,5 mmHg (60%) ( p < 0,001). There was a reduction in glaucoma medications form 3,6 ± 0,6 preoperatively to 1,5 ± 1,1 at 6 months p < 0,001). There were no cases of serious complication as hypotony. Conclusions: Micropulse transscleral cyclophotocoagulation plus is effective and safety in lowering intraocular pressure in eyes with refractory glaucoma after previous failed micropulse transscleral photocoagulation.